If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y(y + -5) = y + 1 Reorder the terms: -2y(-5 + y) = y + 1 (-5 * -2y + y * -2y) = y + 1 (10y + -2y2) = y + 1 Reorder the terms: 10y + -2y2 = 1 + y Solving 10y + -2y2 = 1 + y Solving for variable 'y'. Reorder the terms: -1 + 10y + -1y + -2y2 = 1 + y + -1 + -1y Combine like terms: 10y + -1y = 9y -1 + 9y + -2y2 = 1 + y + -1 + -1y Reorder the terms: -1 + 9y + -2y2 = 1 + -1 + y + -1y Combine like terms: 1 + -1 = 0 -1 + 9y + -2y2 = 0 + y + -1y -1 + 9y + -2y2 = y + -1y Combine like terms: y + -1y = 0 -1 + 9y + -2y2 = 0 Begin completing the square. Divide all terms by -2 the coefficient of the squared term: Divide each side by '-2'. 0.5 + -4.5y + y2 = 0 Move the constant term to the right: Add '-0.5' to each side of the equation. 0.5 + -4.5y + -0.5 + y2 = 0 + -0.5 Reorder the terms: 0.5 + -0.5 + -4.5y + y2 = 0 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + -4.5y + y2 = 0 + -0.5 -4.5y + y2 = 0 + -0.5 Combine like terms: 0 + -0.5 = -0.5 -4.5y + y2 = -0.5 The y term is -4.5y. Take half its coefficient (-2.25). Square it (5.0625) and add it to both sides. Add '5.0625' to each side of the equation. -4.5y + 5.0625 + y2 = -0.5 + 5.0625 Reorder the terms: 5.0625 + -4.5y + y2 = -0.5 + 5.0625 Combine like terms: -0.5 + 5.0625 = 4.5625 5.0625 + -4.5y + y2 = 4.5625 Factor a perfect square on the left side: (y + -2.25)(y + -2.25) = 4.5625 Calculate the square root of the right side: 2.136000936 Break this problem into two subproblems by setting (y + -2.25) equal to 2.136000936 and -2.136000936.Subproblem 1
y + -2.25 = 2.136000936 Simplifying y + -2.25 = 2.136000936 Reorder the terms: -2.25 + y = 2.136000936 Solving -2.25 + y = 2.136000936 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2.25' to each side of the equation. -2.25 + 2.25 + y = 2.136000936 + 2.25 Combine like terms: -2.25 + 2.25 = 0.00 0.00 + y = 2.136000936 + 2.25 y = 2.136000936 + 2.25 Combine like terms: 2.136000936 + 2.25 = 4.386000936 y = 4.386000936 Simplifying y = 4.386000936Subproblem 2
y + -2.25 = -2.136000936 Simplifying y + -2.25 = -2.136000936 Reorder the terms: -2.25 + y = -2.136000936 Solving -2.25 + y = -2.136000936 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2.25' to each side of the equation. -2.25 + 2.25 + y = -2.136000936 + 2.25 Combine like terms: -2.25 + 2.25 = 0.00 0.00 + y = -2.136000936 + 2.25 y = -2.136000936 + 2.25 Combine like terms: -2.136000936 + 2.25 = 0.113999064 y = 0.113999064 Simplifying y = 0.113999064Solution
The solution to the problem is based on the solutions from the subproblems. y = {4.386000936, 0.113999064}
| 2z=3(14-z)+3 | | 30n+7=205 | | 15+63x+7X^2-x^3=0 | | 4x+(3x-11)=10 | | 2y^2+y^2=6 | | x^2-520+3x=0 | | 3-(b+3)=5-b | | -6n-3=9 | | 2cos^2=3/2 | | 2y-10x=-4 | | 100-x=x+1 | | 35=7+7x | | 35=7+7c | | 11+2x=3(2-x) | | x+3-2x=35+x | | x+(0.18*x)=160 | | f(x)=2x^2-11x | | 1/(2e^4x) | | 3x+6y=35.3 | | 4j=-8 | | x-7=12x-106 | | 5y-2=47-7 | | 4x^2+6y^2=8 | | 10x-45=3x-55 | | -25+(-57)= | | 7-6x=9x-36 | | 28+(-32)= | | x-15x/100 | | Tn=12+3n | | 12+11=123 | | 3x+34=11x-65 | | (x+2)+ln(x-2)=ln(21) |